Inflammatory and homeostatic roles of eosinophil subpopulations in chronic rhinosinusitis with nasal polyp pathogenesis - Simmalee, Kantapat; Lumjiaktase, Putthapoom; Kawamatawong, Theerasuk; Guemari, Amir; Dormoy, Valérian; Vitte, Joana (Frontiers in Immunology, 2025)
Chronic rhinosinusitis (CRS) with nasal polyps (CRSwNP) mainly expresses type-2 endotype, featuring eosinophils as a main player in the inflammatory process. Prolonged eosinophilia in the tissues of asthma and CRSwNP patients has been associated with structural changes, leading to fixed airflow obstruction in asthma and nasal polyposis in CRSwNP. This suggests that eosinophils may belong to different subgroups playing distinct roles in pathogenesis. Recent studies highlight the roles of inflammatory eosinophils (iEOS) in driving inflammation and tissue damage, whereas tissue-resident eosinophils (rEOS) maintain homeostasis and tissue repair in the airway. Therefore, understanding both roles of eosinophil subpopulations is crucial for better CRSwNP management, including enhancing the diagnosis accuracy, predicting recurrence, and optimizing treatment strategies.